Modern approaches to physical rehabilitation of children, who often suffer from acute respiratory infections. - Khrystova T.E (Kharkov National Pedagogical University, 2012)
There it is described a comprehensive program of physical rehabilitation, which aims at the prevention of acute respiratory diseases in children of primary school age. The research involved 106 children aged 6-9 years. Comprehensive program of physical rehabilitation included: aromafitotherapy and cryomassage of feet. The research proves that using of the mentioned methods leads to improving health, a significant decrease in throat hyperemia, cough and nasal discharge. It also helps to normalize the indices of breathing and physical development of children. More visible effect was observed while using the essential oils of sage and composition of essential oils (sage, lavender, mint). It is proved that the use of aromafitotherapy and cryomassage of feet helps to reduce the frequency of acute respiratory infections and exacerbations of chronic diseases of children upper respiratory organs at age of 6-12 months. It significantly reduces the number of days when children have to be absent at school because of illness.